2009
DOI: 10.1136/bjo.2008.151522
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of glaucoma medical therapy in a Glasgow teaching hospital: 26 years' experience

Abstract: A large and unique treatment database has been established at the Glaucoma Clinic of Glasgow Royal Infirmary. Containing data spanning a 26-year period, it promises to be an invaluable resource for audit and research. It has already demonstrated its worth by informing changes in prescribing practice that have resulted in direct patient benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…Although definitions of persistency may differ slightly between studies, these findings are similar to those found in large, retrospective studies in the literature 13–16. This may be due to much lower rates of adverse effects with latanoprost than other medications as we have reported in a previous study 11. Latanoprost continues to be the most prescribed drug in our clinic, as can be seen in figure 2B.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although definitions of persistency may differ slightly between studies, these findings are similar to those found in large, retrospective studies in the literature 13–16. This may be due to much lower rates of adverse effects with latanoprost than other medications as we have reported in a previous study 11. Latanoprost continues to be the most prescribed drug in our clinic, as can be seen in figure 2B.…”
Section: Discussionsupporting
confidence: 56%
“…We have previously described, in this journal, a large and unique computerised database established at the glaucoma clinic at Glasgow Royal Infirmary, with data now spanning 27 years 11. We now present our findings on treatment persistence in patients on glaucoma medical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer than 3% of subjects discontinued the FC due to an ocular adverse event. The tolerability of an ocular hypotensive agent is important given the negative impact of ocular adverse events on patient continuation with therapy [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously described, in this journal, a large and unique computerised database established at the glaucoma clinic at Glasgow Royal Infirmary, with data now spanning 27 years 8 9. We now present our findings on the total direct healthcare-related costs for glaucoma management in a population of patients for whom we have complete lifetime data.…”
Section: Introductionmentioning
confidence: 99%